An Investigation on the Influence of Hyaluronic Acid on Polidocanol Foam Stability. Issue 1 (January 2016) - Chen, An-Wei; Liu, Yi-Ran; Li, Kai; Liu, Shao-Hua
Abstract : BACKGROUND: Foam sclerotherapy is an effective treatment strategy for varicose veins and venous malformations. Foam stability varies according to foam composition, volume, and injection technique. OBJECTIVE: To evaluate the stability of polidocanol (POL) foam with the addition of hyaluronic acid (HA). MATERIALS AND METHODS: Group A: 2 mL of 1% POL + 0 mL of 1% HA + 8 mL of air; Group B: 2 mL of 1% POL + 0.05 mL of 1% HA + 8 mL of air; Group C: 2 mL of 1% POL + 0.1 mL of 1% HA + 8 mL of air. Tessari's method was used for foam generation. The half-life, or the time for a volume of foam to be reduced to half of its original volume, was used to evaluate foam stability. Five recordings were made for each group. RESULTS: The half-life was 142.8 (±4.32) seconds for 1% POL without the addition of HA, 310.6 (±7.53) seconds with the addition of 0.05 mL of 1% HA, and 390.4 (±13.06) seconds with the addition of 0.1 mL of 1% HA. CONCLUSION: The stability of POL foam was highly increased by the addition of small amounts of HA.